2020
DOI: 10.38205/imcr.010207
|View full text |Cite
|
Sign up to set email alerts
|

Mindfulness and yoga halt the conversion of pre-diabetic rural women into diabetics-a pilot study

Abstract: Background and Purpose: A plethora of studies have been conducted in the past, which have proven the salutary effects of yoga practice. Yoga and other mind body techniques are deemed as stress relievers and have shown therapeutic effectiveness in preventing the development and progression of several lifestyle diseases including Diabetes. Yoga practice may help in managing Diabetes by regulating the glucose levels in blood. In this study we have evaluated the efficacy of three months of AYUSH-approved Diabetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
(34 reference statements)
0
4
0
Order By: Relevance
“…The present study showed significant improvement in general health status, physical, mental, and environmental health, and overall quality of life after yoga practice. A study by Kaur et al showed significant improvement in general health, social health, and psychological domain of WHOQOL, overall quality of life in yoga group after 3-month DYP in high-risk for diabetes rural women population (55). In our study, we have been focused on the urban population with both gender, Male and Female.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The present study showed significant improvement in general health status, physical, mental, and environmental health, and overall quality of life after yoga practice. A study by Kaur et al showed significant improvement in general health, social health, and psychological domain of WHOQOL, overall quality of life in yoga group after 3-month DYP in high-risk for diabetes rural women population (55). In our study, we have been focused on the urban population with both gender, Male and Female.…”
Section: Discussionmentioning
confidence: 92%
“…DYP includes starting prayer, Sukshma Vyayamas, Shithililarna Practices, Surya Namaskara, Standing asana, sitting asana, prone, supine asana, Kriya, Pranayama, Meditation, Resolve, and Closing Prayer. The previous study also used the same protocol in the high-risk women population (47).…”
Section: Interventionmentioning
confidence: 99%
“…Several studies have shown the positive effects of yoga in T2DM, although none had used a national consensus protocol [ 33 ]. A study on the effect of pranayama and yogasanas on blood glucose and lipid profile in a two-armed design on 60 patients of T2DM between 35–60 yrs with diabetes recruited from the diabetes clinic of a hospital in Delhi, India, had shown a significant reduction in serum insulin, blood glucose (fasting and postprandial), LDL, TG, and VLDL with an increase in HDL, with insignificant changes in the control group after 45 days [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…the use of yogic techniques as a preventive measure for the treatment and management of diabetes or pre-diabetes. The study shows the beneficial result of yogic practices and witnesses the significant reduction in fasting blood glucose, glycated hemoglobin, body mass index, waist-to-hip ratio, body weight, and stress(Kaur et al, 2020…”
mentioning
confidence: 84%